2004
DOI: 10.2320/matertrans.45.2610
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in RNi<SUB>5</SUB>-H (R = Pr, Nd, Sm and Gd) Systems with Two Hydrogen Pressure Plateaux

Abstract: Pressure-composition (P-C) isotherms of RNi 5 -H (R = Pr, Nd, Sm and Gd) systems show two hydrogen pressure plateaux during hydrogen absorption and desorption. These correspond to the transitions among three phases: one hydrogen solid solution ( phase; RNi 5 H $0:5 ) and two hydrides ( phase; RNi 5 H 3$4 and phase; RNi 5 H 5$7 ). To explore the mechanism of the phase transitions, we investigated the structural changes in RNi 5 -H systems with ex-situ XRD. During hydrogen desorption, the ex-situ XRD profiles sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…The modified space group of full hydride phase is not P6/mmm but P63mc [22,23]. Previously we have found from an ex situ XRD analysis that RNi 5 (R = Pr, Nd and Sm) systems underwent the same phase change from P6/mmm (˛phase) to P63mc ( phase) as in the case of LaNi 5 [24]. In addition, the experimentally determined PCIs in Fig.…”
Section: Hydrogen Site Considerationmentioning
confidence: 71%
See 2 more Smart Citations
“…The modified space group of full hydride phase is not P6/mmm but P63mc [22,23]. Previously we have found from an ex situ XRD analysis that RNi 5 (R = Pr, Nd and Sm) systems underwent the same phase change from P6/mmm (˛phase) to P63mc ( phase) as in the case of LaNi 5 [24]. In addition, the experimentally determined PCIs in Fig.…”
Section: Hydrogen Site Considerationmentioning
confidence: 71%
“…The average and the twice of the standard deviation are (kJ mol −1 ) = −3.81 ± 0.34. The constancy of the relaxation parameter can be explained by the fact that RNi 5 -H (R = Pr, Nd and Sm) systems undergo similar structural changes during the hydrogen desorption [24]. The PCIs obtained by fixing and re-optimizing other parameters are drawn with lines in Fig.…”
Section: Pressure-composition Isotherms and Site Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the RNi 5 -H system, two hydrogen sites correspond to the lower and higher plateaux. 15,16) The novel plateau may be attributed to another site whose size is reversed by the unit cell volume. To determine the size of the hydrogen site, it is necessary to clarify the structure of novel RNi 5 hydrides such as HoNi 5 hydride, with specific reference to the novel plateau.…”
Section: Resultsmentioning
confidence: 99%
“…They both show a doubled unit cell along the c-axis. In two recent studies, the authors concluded that RNi 5 compounds have the same crystal structure (P6/mmm), the same phase change and similar hydrogenation properties [25,26]. Here, we adopt the postulation made by Westlake about the maximum occupancy at each site in a formula unit, and it is given in Table I.…”
Section: Application To Rni 5 -H 2 Systems and Discusionmentioning
confidence: 99%